Pregnancy outcomes in women with vaginal bleeding in early pregnancy - Dimple Bhatti; Tapasya Dhar; Kavita Mandrelle; Inderpreet Sohi (Wolters Kluwer Medknow Publications, 2022)
Background: Vaginal bleeding in early pregnancy is a common complaint of pregnant women and its incidence has been reported as 16% to 25%. About half of the patients with vaginal bleeding will abort and remaining poor pregnancy outcomes such as preterm delivery, preterm premature rupture of membranes (PPROM), and intrauterine fetal growth restriction can occur. Aims and Objectives: To study the association of vaginal bleeding in early pregnancy as a useful indicator of pregnancies at risk and to determine the associated perinatal outcome and pregnancy complications. Materials and Methods: A 1-year retrospective study was conducted on a total of 360 patients, comprising 120 women with early pregnancy bleeding and 240 women without bleeding. Pregnancy complications and perinatal outcomes were compared between these two groups of pregnant patients. Results: Out of 120 cases with early pregnancy bleeding, 52.88% aborted, and 47.12% continued their pregnancy beyond 20 weeks. Among those cases that reached beyond 20-week gestation, 48.98% of women delivered prematurely (<37 weeks) and 51.02% delivered at term. Women with vaginal bleeding had onset of preterm labor in 32.65%, antepartum hemorrhage in 18.37%, placenta previa in 8.16%, and low birth weight babies in 53.06% of cases. In contrast, cases without vaginal bleeding in early pregnancy had preterm labor in 2.92%, antepartum hemorrhage in 1.67%, placenta previa in 0.42%, and low birth weight babies in 10.83% of cases. Conclusion: Bleeding in early pregnancy increases the risk of pregnancy complications such as preterm delivery, abortion, antepartum hemorrhage, placenta previa, PPROM, fetal growth restriction, and low birth weight in neonates. Therefore, it is a useful indicator of pregnancy complications and adverse outcomes.